Medical care at the end of life : a Catholic perspective - Kelly, David F. (Georgetown University Press, 2006)
For over thirty years, David F. Kelly has worked with medical practitioners, students, families, and the sick and dying to confront the difficult and often painful issues that concern medical treatment at the end of life. In this short and practical book, Kelly shares his vast experience, providing a rich resource for thinking about life's most painful decisions. Kelly outlines eight major issues regarding end-of-life care as seen through the lens of the Catholic medical ethics tradition. He looks at the distinction between ordinary and extraordinary means; the difference between killing and a.